Relation between Multiple Markers of Work-Related Fatigue - Ina Völker; Christine Kirchner; Otmar L. Bock (Elsevier, 2016)
Background: Work-related fatigue has a strong impact on performance and safety but so far, no agreed upon method exists to detect and quantify it. It has been suggested that work-related fatigue cannot be quantified with just one test alone, possibly because fatigue is not a uniform construct. The purpose of this study is therefore to measure work-related fatigue with multiple tests and then to determine the underlying factorial structure. Methods: Twenty-eight employees (mean: 36.11; standard deviation 13.17) participated in five common fatigue tests, namely, posturography, heart rate variability, distributed attention, simple reaction time, and subjective fatigue before and after work. To evaluate changes from morning to afternoon, t tests were conducted. For further data analysis, the differences between afternoon and morning scores for each outcome measure and participant (Δ scores) were submitted to factor analysis with varimax rotation and each factor with the highest-loading outcome measure was selected. The Δ scores from tests with single and multiple outcome measures were submitted for a further factor analysis with varimax rotation. Results: The statistical analysis of the multiple tests determine a factorial structure with three factors: The first factor is best represented by center of pressure (COP) path length, COP confidence area, and simple reaction time. The second factor is associated with root mean square of successive difference and useful field of view (UFOV). The third factor is represented by the single Δ score of subjective fatigue. Conclusion: Work-related fatigue is a multidimensional phenomenon that should be assessed by multiple tests. Based on data structure and practicability, we recommend carrying out further studies to assess work-related fatigue with manual reaction time and UFOV Subtest 2.